The Implementation of Chemical Castration for Pedophilia Offenders in The Review of Law No.17 Of 2016 And Islamic Criminal Law - Khoirul Ikhsan Al amanah; Sudirman Suparmin (Warmadewa Press, 2024)
This study looks at the Law No. 17/2016's provisions regarding chemical castration as a penalty for pedophilia and contrasts them with Islamic criminal law. This study examines pertinent laws and literature using a normative juridical framework to determine the acceptability and efficacy of chemical castration. The research findings reveal that chemical castration, as an additional punishment in Law No. 17/2016, aims to provide a deterrent effect and protect victims from sexual crimes. However, from the perspective of Islamic criminal law, there are significant differences regarding the permissibility and effectiveness of this punishment, which emphasizes justice, victim recovery, and proportional punishment. This study concludes that although chemical castration is considered a preventive measure in Indonesia's positive legal system, its implementation needs to be further considered in order to comply with the principles of justice in Islamic criminal law.